Porous alumina scaffolds chemically modified by calcium phosphate minerals and their application in bone grafts - Silva, Andre D. R.; Rigoli, Willian R.; Mello, Daphne C. R. [UNESP]; Vasconcellos, Luana M. R. [UNESP]; Pallone, Eliria M. J. A.; Lobo, Anderson O. (Wiley-Blackwell, 2019)
The chemical modification of porous ceramic scaffold surfaces with calcium phosphate surges as an alternative to improve the bioactivity to be used as bone grafts. The biomimetic method has been commonly used to modify surfaces of Ti alloys but surges as alternative to modify ceramic biomaterials. Herein, we modified the surface of Al2O3 scaffolds with calcium phosphate minerals and strontium using the biomimetic method. The scaffolds were chemically treated using H3PO4 solution and then immersed in simulated body fluid 5x solution for 14 days. For the incorporation of strontium, they were immersed in an aqueous solution of 100 ppm analytical-grade Sr(NO3)(2) under magnetic stirring. The samples were characterized by scanning electron microscopy, X-ray microtomography, X-ray diffraction, near-infrared spectroscopy, inductively coupled plasma emission spectroscopy, and energy-dispersive X-ray spectroscopy. The biocompatibility and ability to differentiate osteoblasts in vitro were evaluated using human cells. The incorporation of strontium into the phosphate structure was verified. Scaffolds were obtained with high porosity, three-dimensional structures, and the preferential adhesion and maturation of osteoblastic cells, which are essential to promote bone regeneration in vivo.
Keywords: bioactivity; calcium phosphate; scaffolds; surface modification